1996
DOI: 10.1088/0268-1242/11/4/007
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy- and acceptor-H complexes in InP

Abstract: Abstract. It has been suggested that iron in InP is compensated by a donor, related to the 2316 cm −1 local vibrational mode and previously assigned to the fully hydrogenated indium vacancy, V In H 4 . Using AIMPRO, an ab initio local density functional cluster code, we find that V In H 4 acts as a single shallow donor. It has a triplet vibrational mode at around this value, consistent with this assignment. We also analyse the other hydrogenated vacancies V In H n , n = 1, 3, and determine their structure, vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 22 publications
6
33
0
Order By: Relevance
“…In as-grown [13][14][15] and H-implanted 16 InP there is a strong band at 2316 cm -1 that has been assigned to a P-H stretching mode of a V In -H 4 complex. 14,15,17 A lower frequency band at 2201 cm -1 has also been assigned to a P-H stretching mode of V In -H. 14,17,18 Additional weak lines have been seen between these frequencies. 14, 16 Ewels et al 17 have calculated the frequencies of the V In -H n complexes and have proposed that the partial dissociation of the V In -H 4 complex upon annealing leads to the formation of V In -H n centers with fewer H atoms, and thus lower frequencies, to explain the presence of several Hstretching bands.…”
Section: Vibrational Spectroscopymentioning
confidence: 96%
See 2 more Smart Citations
“…In as-grown [13][14][15] and H-implanted 16 InP there is a strong band at 2316 cm -1 that has been assigned to a P-H stretching mode of a V In -H 4 complex. 14,15,17 A lower frequency band at 2201 cm -1 has also been assigned to a P-H stretching mode of V In -H. 14,17,18 Additional weak lines have been seen between these frequencies. 14, 16 Ewels et al 17 have calculated the frequencies of the V In -H n complexes and have proposed that the partial dissociation of the V In -H 4 complex upon annealing leads to the formation of V In -H n centers with fewer H atoms, and thus lower frequencies, to explain the presence of several Hstretching bands.…”
Section: Vibrational Spectroscopymentioning
confidence: 96%
“…14,15,17 A lower frequency band at 2201 cm -1 has also been assigned to a P-H stretching mode of V In -H. 14,17,18 Additional weak lines have been seen between these frequencies. 14, 16 Ewels et al 17 have calculated the frequencies of the V In -H n complexes and have proposed that the partial dissociation of the V In -H 4 complex upon annealing leads to the formation of V In -H n centers with fewer H atoms, and thus lower frequencies, to explain the presence of several Hstretching bands. Similarly, in our GaN studies, we suggest that the N-H stretching modes we observe belong to a family of V Ga -H n complexes.…”
Section: Vibrational Spectroscopymentioning
confidence: 96%
See 1 more Smart Citation
“…If H and D are present in the samples and the V In H 4 complex can be formed, then a total of five different types of complexes should exist by replacing H by D: H 4 , H 3 D, H 2 D 2 , HD 3 , and D 4 . By ab initio local-density-functional pseudopotential calculations using an 131-atom InP cluster, the vibrational frequencies of these five types of complexes have been evaluated [9]. There is one infrared active hydrogen stretching mode for H 4 , two for H 3 D and H 2 D 2 , one for HD 3 , and the corresponding numbers for the deuterium stretching modes.…”
Section: The V In H 4 Complexmentioning
confidence: 99%
“…For complexes with more than one H atom, the mode pattern is more complicated. Calculations for the V In H 4 complex have shown [9] that in InP:H:D samples six lines in the region of the H-stretching modes and additionally six lines in the region of the D-stretching modes are expected. First experiments on InP:H:D [10] showed that around the 2315.6 cm -1 line three additional lines are detected, while two lines appear in the region of the corresponding deuterium modes.…”
Section: Introductionmentioning
confidence: 99%